Research on Risk Management Strategies and Implementation Paths in Chip Design - Liu, Chengye (Academic Journal of Sociology and Management, 2024)
Chip design has emerged as an essential field due to the increasing complexity of semiconductor systems and demand for faster, more cost-effective solutions across industries. Unfortunately, chip production comes with many risks, from technical challenges to market volatility - making risk management an essential aspect of chip design process. This paper offers comprehensive risk management strategies within chip design; specifically identifying, evaluating and mitigating risks through effective management practices throughout its life cycle - ultimately guaranteeing efficient project execution and management.